Моделювання амплітудно-частотних характеристик вібраційних систем з електромагнітним приводом - Гурський, Володимир; Ланець, Олена (Видавництво Львівської політехніки, 2011)
Розглянуто принципи та методи чисельного моделювання амплітудно-частотних характеристик вібраційних систем з електромагнітним приводом. В основу покладено диференціальні рівняння, що описують коливальні процеси в електромагнітній системі. На основі методу комплексних амплітуд здійснюється перехід до системи нелінійних алгебричних рівнянь з амплітудними значеннями параметрів, яка розв’язується відомими числовими методами Ньютона, Левенберга та ін. На основі отриманих розв’язків графічно будуються амплітудно-частотні характеристики коливальних мас механічної та сили струму електромагнітної складових вібраційної системи. The vibratory systems in practice can be presented as a various executive devices, technological vibratory machines, etc. In an engineer and building industry, for disturbance of high-frequency vibrations (50-100 Hertz), electromagnetic drive and resonance effects, appropriate to the mechanical systems are used. Work of the vibratory systems can be estimated on many indexes. One of them is an index of expenses of power on a square of vibration amplitude of executive mass (W/mm2). As vibratory systems can be multimass, that is why for a quantitative estimation it is necessary to have gain-frequency descriptions of mechanical and electromagnetic constituents. Researches of gain-frequency descriptions of the three-masses mechanical systems allowed to find out the important energy efficient methods of calculation of resiliently hard parameters [1]. In a number of other works [2, 3] theoretical researches of electromagnetic processes and their designs are given in more simple structure – of two-masses electromechanics systems. Using of the known numerical methods and their adaptation to the tasks of dynamics will allow to analyze the indexes of effective work of the three-masses oscillating systems. Principles and methods of numeral design of gainfrequency descriptions of the oscillating systems with an electromagnetic drive are considered. Differential equations which describe oscillating processes in the electromagnetic system are fixed in basis of principle. On the basis of method of complex amplitudes passing is carried out to the system of nonlinear algebraic equations, which is untied by the known numerical methods of Newton, Levenberg etc. On the basis of the got solutions the gain-frequency descriptions of oscillating masses of mechanical and strength of current of electromagnetic constituents of the oscillating system are graphical built. Gain-frequency dependences enable to analyze and set the rational modes of work last after the set power or dynamic criteria are got.
Frequency response modelling of vibratory electromagnetic drive systems
Keywords: вібраційна система; амплітудно-частотні характеристики; числові методи; електромеханічний резонанс; електромагнітний привод